The influence of cross-winds on the performance of natural draft dry-cooling towers. - Du Preez, Abraham Francois (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 1992.